Early Financial Literacy Education: Savings and Personal Financial Planning Training for Students of Hang Tuah 2 Private Junior High School Medan - Nissa, Fachrun; Eddy Harnjo; Amin Hou; Roni Juliansyah; Ahmad Rivai; Dini M Hutagalung; Indra Budiman; Sabaruddin Chaniago; Muhammad Fathoni; Ratih Amelia (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
This community service activity aims to improve financial literacy among junior high school students through training in saving habits and personal financial planning. Targeting students at SMP Hang Tuah Medan, the program introduces basic financial concepts such as budgeting, distinguishing needs from wants, setting financial goals, and managing allowances. The method used combines interactive workshops, simulations, and group discussions to foster a fun and engaging learning experience. Through this initiative, students are expected to develop awareness of financial responsibility from an early age and apply simple financial management practices in their daily lives. The program also supports the development of life skills and contributes to character education by promoting discipline, self-control, and decision-making. The outcome of the activity indicates a significant improvement in students’ understanding and attitudes toward money management. This initiative highlights the importance of integrating financial literacy education into the school environment to build a financially literate generation